2015
DOI: 10.1186/s13028-016-0213-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of litter size on sow stayability in Swedish commercial piglet producing herds

Abstract: BackgroundSows’ ability to produce an excessive amount of piglets has shaped modern piglet production and there has been a steady increase in litter size during the last decades. This development has caused some negative side-effects, such as an increase in the proportion of stillborn piglets, a decrease in the proportion of weaned piglets and a larger variation in quality of piglets. Swedish commercial piglet producing herds have, like other countries with high production levels, high piglet mortality and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Culling reasons were grouped into four categories: ‘reproductive failure,’ ‘lameness,’ ‘high parity’ and ‘others.’ Reproductive failure included no estrus, failure to farrow, found not pregnancy and abortion. The high parity culling category was restricted to sows of parity ≥4 at culling, because the median culling parity was 4, and so a planned culling for “high parity” could not be the reason for culling in a low parity [ 14 ]. Therefore, any low-parity sows recorded as being culled for high parity were regarded as missing records.…”
Section: Methodsmentioning
confidence: 99%
“…Culling reasons were grouped into four categories: ‘reproductive failure,’ ‘lameness,’ ‘high parity’ and ‘others.’ Reproductive failure included no estrus, failure to farrow, found not pregnancy and abortion. The high parity culling category was restricted to sows of parity ≥4 at culling, because the median culling parity was 4, and so a planned culling for “high parity” could not be the reason for culling in a low parity [ 14 ]. Therefore, any low-parity sows recorded as being culled for high parity were regarded as missing records.…”
Section: Methodsmentioning
confidence: 99%
“…Since then, litter size and farrowing duration increased steadily [1]. Nowadays, sows are hyperprolific (average litter size > 16) with an average farrowing duration of longer than 300 min [1][2][3][4][5][6][7]. This means that more than half of all parturitions are longer than physiologically.…”
Section: Parturition and Birth Complicationsmentioning
confidence: 99%
“…This means that more than half of all parturitions are longer than physiologically. This rapid increase is concerning and leads to a high incidence of dystocia with subsequent negative consequences on piglet survival and sows' fertility and longevity [1][2][3][4][5][6][7]. An older survey showed that dystocia was mostly of maternal origin [8], whereas a newer survey identified that dystocia is nowadays almost exclusively due to maternal causes; with uterine inertia being the most common cause [9].…”
Section: Parturition and Birth Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In pig breeding, reproduction performance, particularly female reproductive performance, is a very important economic trait [1]. Reproductive traits are complex, and desirable reproductive phenotypes, such as litter size, are true polygenetic traits affected by interactions between multiple genes and the environment [2-5]. Each individual gene contributes to the overall variation in these traits [3, 6].…”
Section: Introductionmentioning
confidence: 99%